Decannulation in children affected by congenital central hypoventilation syndrome: A proposal of an algorithm from two European centers. Issue 11 (16th July 2019) - Paglietti, Maria Giovanna; Porcaro, Federica; Sovtic, Aleksandar; Cherchi, Claudio; Verrillo, Elisabetta; Pavone, Martino; Bottero, Sergio; Cutrera, Renato
Abstract: Rationale: Long‐life ventilatory assistance is necessary for survival in pediatric patients with congenital central hypoventilation syndrome (CCHS). Invasive mechanical ventilation (IMV) through tracheostomy is the most used method, especially in the first years of life when the central nervous system is maturing. Nevertheless, IMV via tracheostomy is not ideal because tracheostomy in children is associated with impaired speech and language development, also frequent infections of the lower airway tract occur. Objective: Only few reports describe the transition from IMV to the noninvasive method, ending with decannulation in CCHS affected patients. We aim to provide our experience regarding decannulation program in CCHS affected children and to describe a proposal of an algorithm concerning transition from invasive to noninvasive ventilation (NIV) in CCHS patients. Methods: The study has been conducted retrospectively. Four children from two European centers underwent tracheostomy removal and decannulation, upon request of patients and their families. Results: All children were trained to carry out tracheostomy capping before decannulation and underwent endoscopic assessment of upper and lower airway. Subsequently they started training to NIV at mean age of 106.25 months (±40.7 SD). Decannulation occurred 12 months after and no patients needed the reintroduction of tracheal cannula in either short or long term follow up. Conclusions: our study shows that effective liberation from IMV, the transition to NIV and decannulation are possible in CCHS affected children and offers a proposal of an algorithm which can be applied in selected centers.